Penguatan Literasi Teknologi dan Inovasi Pembelajaran Berbasis AI Bagi Guru Sekolah Dasar di KKG Dabin 2 Jepara - Kukuh Dwi Wijanarko; Alzena Dona Sabilla; Hamidaturrohmah Hamidaturrohmah; Santi Andriyani; Noor Azizah; Azzah Noor Laila (CV. Global Cendekia Inti, 2026)
Technology literacy and understanding of artificial intelligence have become essential competencies for elementary school teachers in creating innovative and relevant learning experiences in today’s rapidly evolving era. This community service activity aimed to improve digital literacy, understanding of artificial intelligence, and skills in utilizing digital learning media among teachers who are members of the Dabin 2 Teacher Working Group in Jepara District. The activity was conducted at Jobokuto Elementary School, Jepara, through seminars, interactive discussions, workshops, and hands-on practice in the use of artificial intelligence, Augmented Reality-based learning media, and simple programming introduction using Scratch. Evaluation using a Likert-scale questionnaire completed by 64 participants showed highly positive responses. Most participants stated that the activity was beneficial in improving teachers’ professional competence. The results indicated that the training enhanced teachers’ readiness to utilize digital technology as a learning medium and should be followed up through continuous mentoring to optimize classroom implementation